2013
DOI: 10.5152/akd.2013.072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of right ventricular functions in patients with nasal polyposis: an observational study

Abstract: Objective: The aim of this study was to assess the right ventricular functions in patients with nasal polyposis using the strain (S) and strain rate (SR) echocardiography. Methods: A prospective, cross-sectional observational study was performed. The study included 40 patients with nasal polyposis (NP) (Group 1), and 25 healthy controls (Group 2). The study comprised patients with Stage 2 and Stage 3 nasal obstruction and no symptoms that could be associated with right ventricular heart failure. Longitudinal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…RV systolic and diastolic dysfunction is common in patients with HF and is associated with a poor long-term prognosis (16-19). The MPI, which is also known as the Tei index, has been described as a non-invasive measurement of ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…RV systolic and diastolic dysfunction is common in patients with HF and is associated with a poor long-term prognosis (16-19). The MPI, which is also known as the Tei index, has been described as a non-invasive measurement of ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting investigating subclinical dysfunction with the strain (S technology) and strain rate (SR). In 2013 a study [4] was performed, in which echocardiography S and SR showed a subclinical deficiency of the longitudinal right functions in patients with nasal polyposis, where a simple echocardiogram showed no alterations of the right sections [4].…”
Section: Archives Of Medicine Issn 1989-5216mentioning
confidence: 99%
“…Apart from the unlikely possibility that this association is due to chance, there are at least two plausible interpretations [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, thank you for your comments about our paper published in The Anatolian Journal of Cardiology (1).If the patients with nasal polyposis left untreated, it could affect firstly right ventricle functions and then it could cause cardiovascular complications. However, at the present time there is not any cut-off value (for hypoxia and pulmonary arterial pressure value) for these cardiovascular complications.…”
mentioning
confidence: 99%
“…Firstly, thank you for your comments about our paper published in The Anatolian Journal of Cardiology (1).…”
mentioning
confidence: 99%